Spatial Disparity in Status and performance of Health Care Services in Bardhaman District, W.B. - Mahata, Sangita; Sharma, V.N. (National Geographical Journal of India, 2022)
This paper attempts to find out the spatial variation in status and performance of health care services in Bardhaman district of West Bengal. In so doing, two important indices are considered, namely, Health Input Index (HII) and Health Output Index (HOI) to evaluate the status and performance of various health care services respectively across the study area. To explore the interrelationships between both indices among the blocks Spearman's correlation and coefficient of variation analysis are carried out. The study summaries that the correlation is positive between Health Input (HII) and output Index (HOI).